2007
DOI: 10.1109/iembs.2007.4352806
|View full text |Cite
|
Sign up to set email alerts
|

Electrovestibulography: The "DC" potential used to separate Meniere's disease and Benign Paroxysmal Positional Vertigo

Abstract: Electrovestibulography (EVestG) is a new diagnostic technique potentially applicable to detecting neurological changes impacting on sensory performance. A complex Morlet wavelet based signal processing technique, a Neural Event Extraction Routine, has been used to extract diagnostically meaningful biomarkers from these EVestG recordings. Separation of Meniere's disease and Benign Paroxysmal Positional Vertigo (BPPV) has been accomplished using a "DC" Biomarker [1]. When using tilt stimuli to evoke a semi circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Previous studies suggested that EVestG responses are sensitive to alterations of neural activity in Parkinson's subjects (which might arise from disrupted brain DA systems) [12] as well as conditions relating directly to vestibular disturbance like Meniere's disease and Benign Paroxysmal Positional Vertigo [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that EVestG responses are sensitive to alterations of neural activity in Parkinson's subjects (which might arise from disrupted brain DA systems) [12] as well as conditions relating directly to vestibular disturbance like Meniere's disease and Benign Paroxysmal Positional Vertigo [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among the EVestG tilts, the supine up/down tilt predominantly stimulates the utricular organ, and together with the sitting up/down tilt, which mainly stimulates the saccule, contains the lowest contribution of muscle artefacts, hemodynamic effects, and participant anxiety. Considering the closeness of the utricular maculae to the stapes and thus to the EVestG recording electrode, it is more likely that the EVestG response is mostly driven from the utricle [59]. Therefore, the selection of the supine up/down tilt for mutual separation of the three aforementioned groups can be considered physiologically and experimentally reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Elelctrovestibulography (EVestG). Although Garrett et al [90] concluded that the separation of the response into acceleration and deceleration might be beneficial in distinguishing between Benign Paroxysmal Positional Vertigo (BPPV) and Meniere's disease, the results suggested that the DC component warrants further analysis [91]. * A thesis in 2014 followed by a paper; both were captured during the screening and data analysis.…”
Section: Functional Biomarkers [Table 2 and 3]mentioning
confidence: 99%